2016
DOI: 10.1080/15622975.2016.1224929
|View full text |Cite
|
Sign up to set email alerts
|

Consensus paper of the WFSBP Task Force on Biological Markers: Criteria for biomarkers and endophenotypes of schizophrenia, part III: Molecular mechanisms

Abstract: Large longitudinal cohort studies are essential that pair a thorough phenotypic and clinical evaluation for example with gene expression and proteome analysis in blood at multiple time points. This approach might identify biomarkers that allow patients to be stratified according to treatment response and ideally also allow treatment response to be predicted. Improved knowledge of molecular pathways and epigenetic mechanisms, including their potential association with environmental influences, will facilitate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 260 publications
1
22
0
Order By: Relevance
“…Interestingly, we also observed increased HDAC1 levels in blood samples from mice exposed to ELS and in patients with schizophrenia. Although increased HDAC1 levels in blood are unlikely to contribute to schizophrenia-like phenotypes, this finding is in line with the view that adverse early life events and other risk factors induce similar gene expression changes in various cell types (46).…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, we also observed increased HDAC1 levels in blood samples from mice exposed to ELS and in patients with schizophrenia. Although increased HDAC1 levels in blood are unlikely to contribute to schizophrenia-like phenotypes, this finding is in line with the view that adverse early life events and other risk factors induce similar gene expression changes in various cell types (46).…”
Section: Discussionsupporting
confidence: 72%
“…Blood-based studies of the ARMS and UHR, focusing on inflammation markers, have been undertaken and have shown largely consistent changes implicating a proinflammatory process in both psychosis and affective disorder [8,9]. These findings are supported and extended by discovery proteomic studies of first episode psychosis and schizophrenia implicating the acute-phase response, glucocorticoid receptor signalling, coagulation, and lipid and glucose metabolism [10,11]. Furthermore, inflammatory cytokines, chemokines, and growth factors have been assessed in the blood during the perinatal periods and during childhood in subjects who subsequently developed schizophrenia, and in those with a first episode psychosis [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 86%
“…These conflicting results could at least partly be explained by differences in durations of illness between study samples since a positive correlation was observed between duration of illness and betaine concentrations [16] . Despite this research, a generally approved biomarker (panel) for schizophrenia still remains to be identified [18] .…”
Section: Introductionmentioning
confidence: 99%